The terrorist threat to the maritime security of the UAE - Burke, Paul (Emirates lecture series, 2010)
"The maritime sector in the Arabian Gulf is vital to the economic security of the United Arab Emirates (UAE), yet it remains a stated target of terrorist attack. Around 85 percent of the Middle East's total oil exports (around 17 million barrels per day) pass through the Strait of Hormuz. The vast size and scale of the maritime domain makes it difficult to secure and to police. The world's maritime industry carries the bulk of intercontinental trade, estimated at around 90 percent of the volume and 85 percent of the value. The threat spectrum is wide and continues to increase."--Publisher Summary